A Collection Turíbio Santos: o intérprete/editor e o desafio na construção de novo repertório brasileiro para violão - Celso Silveira Faria (2012)
During the 1970s and 1980s, the Brazilian guitarist Turíbio Santos signed a collection at Éditions Max Eschig. At a certain point, Turíbio glimpsed the possibility of creating a new repertoire for the instrument and comissioned some works to seven brazilian composers. This collection can be considered a relevant sampling of the brazilian guitar composition at that time. The heterogeneity of these works reflects, on the other hand, different knowledge and pratice of each composer in relation to the guitar. The interviews showed that the guitarist acted only in the proposition of the fingering in each work, without interfere in the final result of the musical pieces. Finally, data were collected to understand why some works have been the immediate approval of interpreters and, hence the public.